Situation Report: Romania, 16 March 1966 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romanian-Hungarian Communique Couve de Murville to Visit Bucharest Economic Delegation in UAR Romanian Economic Exhibition in Moscow Romania Backs East Germany's UN Bid Bughici Speech at Cypriot Party Congress Miscellaneous